Combined search for anomalous pseudoscalar HW couplings in VH(H -> b(b)over-bar) production and H -> VV decay - (:unkn) unknown (ELSEVIER, 2016)
A search for anomalous pseudoscalar couplings of the Higgs boson H to electroweak vector bosons V (= W or Z) in a sample of proton-proton collision events corresponding to an integrated luminosity of 18.9 fb(-1) at a center-of-mass energy of 8 TeV is presented. Events consistent with the topology of associated VH production, where the Higgs boson decays to a pair of bottom quarks and the vector boson decays leptonically, are analyzed. The consistency of data with a potential pseudoscalar contribution to the HVV interaction, expressed by the effective pseudoscalar cross section fractions f(a3), is assessed by means of profile likelihood scans. Results are given for the VH channels alone and for a combined analysis of the VH and previously published H -> VV channels. Under certain assumptions, f(a3)(ZZ) > 0.0034 is excluded at 95% confidence level in the combination. Scenarios in which these assumptions are relaxed are also considered. (C) 2016 The Author. Published by Elsevier B.V. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).
Keywords: CMS; Physics; Higgs; BSM; BROKEN SYMMETRIES; WH